The predator pendulum revisited: Social conflict over wolves and their management in the western United States - Jeremy T. Bruskotter (Wildlife Society Bulletin)
Abstract The reintroduction, recovery, and management of gray wolves (Canis lupus) in the western United States has long been a source of controversy and acrimonious public debate. I discuss 3 factors that perpetuate confusion and conflict over wolves and their management: 1) the role of science and politics in wildlife management, 2) rhetoric and political actions of elected officials and political appointees, and 3) justification of wolf harvest and specific practices employed during hunting and trapping seasons. Wildlife professionals could reduce the controversy surrounding wolves by 1) clearly delineating policy decisions from the scientific input used to inform these decisions; 2) clearly articulating scientific concepts when they are used in agency communications; 3) employing collaborative public‐involvement processes designed to reduce conflicts (e.g., collaborative learning, alternative dispute resolution); and 4) setting hunting and trapping regulations with public input concerning the timing of seasons, and methods and locations of take. Longitudinal studies designed to assess how human attitudes and behaviors change in response to changing policies would be particularly valuable for understanding and potentially reducing conflicts over wolves (and other wildlife) in the future. Such data could be collected through collaborations between social scientists, who possess expertise in relevant research methods and theoretical knowledge, and state Cooperative Fish and Wildlife Research units, who possess experience working with state agencies. © 2013 The Wildlife Society.